YEAST SRP1, A NUCLEAR-PROTEIN RELATED TO DROSOPHILA AND MOUSE PENDULIN, IS REQUIRED FOR NORMAL MIGRATION, DIVISION, AND INTEGRITY OF NUCLEI DURING MITOSIS - Küssel, Polonca; Frasch, Manfred (Molecular and General Genetics MGG, 1995)
This paper describes genes from yeast and mouse with significant sequence similarities to a Drosophila gene that encodes the blood cell tumor suppressor pendulin. The protein encoded by the yeast gene, Srp1p, and mouse pendulin share 42% and 51% amino acid identity with Drosophila pendulin, respectively. All three proteins consist of 10.5 degenerate tandem repeats of similar to 42 amino acids each. Similar repeats occur in a superfamily of proteins that includes the Drosophila Armadillo protein. All three proteins contain a consensus sequence for a bipartite nuclear localization signal (NLS) in the N-terminal domain, which is not part of the repeat structure. Confocal microscopic analysis of yeast cells stained with antibodies against Srp1p reveals that this protein is intranuclear throughout the cell cycle. Targeted gene disruption shows that SRP1 is an essential gene. Despite their sequence similarities, Drosophila and mouse pendulin are unable to rescue the lethality of an SRP1 disruption. We demonstrate that yeast cells depleted of Srp1p arrest in mitosis with a G2 content of DNA. Arrested cells display abnormal structures and orientations of the mitotic spindles, aberrant segregation of the chromatin and the nuclei, and threads of chromatin emanating from the bulk of nuclear DNA. This phenotype suggests that Srp1p is required for the normal function of microtubules and the spindle pole bodies, as well as for nuclear integrity. We suggest that Srp1p interacts with multiple components of the cell nucleus that are required for mitosis and discuss its functional similarities to, and differences from Drosophila pendulin.
Keywords: MITOSIS; CELL CYCLE; NUCLEAR PROTEIN; NLS-RECEPTORS; SRP1